Compressive resistance of concrete produced with recycled concrete aggregate and sugarcane vinasse waste-water - Tamashiro, Jacqueline Roberta; Kinoshita, Angela; Pereira Silva, Lucas Henrique; Friol Guedes de Paiva, Fabio; Antunes, Patricia Alexandra; Simões, Rebeca Delatore [UNESP] (Elsevier, 2022)
Vinasse is the main by-product of the sugar and alcohol industry. For each liter of ethanol produced from sugarcane, approximately 12–18 L of vinasse are generated. Being such, its use as a hydration agent in concretes may be useful to save drinking water. This work analyzed the compressive strength of concrete manufactured with vinasse and recycled concrete aggregates (RCA), as a substitute for water (100%) and sand (50 and 100%), respectively. At the initial periods (7 and 14 days), the compressive strength of specimens hydrated with water was higher than those hydrated with vinasse due to the delay in hydration of the cement caused by the sucrose present in the vinasse. Therefore, in these stages, the hydration agent is the main contributor for the differences in the compression strength (p < 0.05, Two-way ANOVA). In the later stages (21 and 28 days), the RCA content was that which most contributed to the differences in the compressive strength. Specimens with 50% RCA showed the highest values (p < 0.05), independently of the hydration agent; the specimens with vinasse reached the same resistance as that of the reference. After 63 days of curing, the concrete with water replaced by vinasse acquired higher resistance in relation to the reference due to continuity of curing. As both residues proved to be viable in the composition of concretes, they were applied in a precast concrete panel, that presented satisfactory results, enabling its use as a non-structural wall. It can be concluded that sugarcane vinasse with recycled concrete aggregate (RCA) is a suitable solution to achieve better reuse of construction and agroindustry waste as a new building materials compound.
Keywords: Concrete; Mechanical compressive strength; Precast concrete panel; Recycled concrete aggregate; Vinasse